Clinical case of renal and pararenal abscess - S. N. Styazhkina; A. A. Abramovich; I. R. Valeeva; R. R. Timirova (Вестник медицинского института «Реавиз»: Реабилитация, врач и здоровье, 2021)
Renal and pararenal abscesses are rare but serious diseases that result from infection of kidneys or tissues around them. This article examines a clinical case of renal and paranephric abscess, presents modern data on the etiology of the disease, types of abscesses, and describes the mechanisms and risk factors for the development of renal and pararenal abscesses, as well as the main diagnostic measures.